PENERAPAN SISTEM ONLINE DIGITAL SAVING DALAM MENINGKATKAN KEPUASAN NASABAH DI MEDIASI DENGAN KEPUTUSAN MENABUNG (Studi Kasus pada Nasabah PT. BRI Cabang Pelintung Dumai) - Muhalida Zia Ibhar; Frinov Feldiko Ibhar (LPPM STIA Lancang Kuning Dumai, 2023)
This study aims to look at the application of the Online Digital Saving System in Improving Customer Satisfaction Mediation with Saving Decisions. The target population of this study were active savers/customers of PT Bank BRI Pelintung Dumai Branch. This research was conducted with a quantitative research approach. The population in this study amounted to 202 people and the samples were taken using the slovin formula, so the number of samples in this study was 145 respondents. Sampling used random sampling technique. Data analysis in this study used inferential statistical data analysis measured by SEM-PLS. The results of the study show that (1) SODS has a significant effect on saving decisions; (2) SODS has a significant effect on customer satisfaction; (3) The decision to save has a significant effect on customer satisfaction.